Generation and characterization of a monoclonal antibody against human BCL6 for immunohistochemical diagnosis - Jia, Kunzhi (PLoS One, 2019)
BACKGROUND: Human B-cell lymphoma 6 (BCL6) gene, usually coding protein of 706 amino acids, is closely associated with large B cell lymphoma. Researches showed that protein mutation or change of expression levels usually happened in the mounting non-hodgkin lymphoma (NHL). Thus BCL6 is considered to be involved in germinal center (GC)-derived lymphoma. RESULTS: The BCL6(1-350) gene codons were optimized for prokaryotic system. After expression of BCL6(1-350) in E. coli, the BCL6(1-350) protein was purified with Ni column. Then the BCL6(1-350) protein, mixing with QuickAntibody-Mouse5W adjuvant, was injected into Balb/c mice. After immunization and cell fusion, a stable cell line named 1E6A4, which can secrete anti-BCL6 antibody, was obtained. The isotype of 1E6A4 mAb was determined as IgG(2a), and the affinity constant reached 5.12×10(10) L/mol. Furthermore, the specificity of the mAb was determined with ELISA, western blot and immunohistochemistry. Results indicated that the 1E6A4 mAb was able to detect BCL6 specifically and sensitively. CONCLUSIONS: BCL6(1-350) antigen has been successfully generated with an effective and feasible method, and a highly specific antibody named 1E6A4 against BCL6 has been screened and characterized in this study, which was valuable in clinical diagnosis.